The effect of the GASING method on mathematics learning outcomes of fourth-grade students at SDN Kesek 1 - Amma Azizah Munawaroh; Mohammad Edy Nurtamam (Edumaspul: Jurnal Pendidikan, 2025)
This research aims to determine whether there is an effect of using the GASING (Gampang, Asik, Menyenangkan - Easy, Fun, Enjoyable) method on the mathematics learning outcomes of fourth-grade students at SDN Kesek 1. This was a quantitative research study using a Quasi-Experimental Design, specifically a nonequivalent control group design. The research was conducted at SDN Kesek 1 with a total of 28 students. Purposive sampling was used to select the sample. The instruments used were observation sheets and student learning outcome test sheets. Data was collected using post-test questions for both the experimental and control classes. The results of this study indicate that there is an effect of using the GASING method on students' mathematics learning outcomes. Based on the test criteria, if the Sig. (2-tailed) value is < 0.005, then H0 is rejected and Ha is accepted. Additionally, if the t count value > t table (2.062 > 2.055), then H0 is rejected and Ha is accepted. Therefore, it can be concluded that there is an influence from the application of the GASING method on the mathematics learning outcomes of fourth-grade students at SDN Kesek 1.